30-day outcome after orthopaedic surgery in patients assessed as negative for COVID-19 at the time of surgery during the peak of the pandemic - Price, A; Shearman, AD; Hamilton, TW; Alvand, A; Kendrick, B (British Editorial Society of Bone and Joint Surgery, 2020)
Introduction: The aim of this study is to report the 30 day COVID-19 related morbidity and mortality of patients assessed as SARS-CoV-2 negative who underwent emergency or urgent orthopaedic surgery in the NHS during the peak of the COVID-19 pandemic.